Role of Planning and Risk Tolerance as Intervening Constructs Between Financial Well-Being and Financial Literacy among Professionals - D. Arpana; H.R. Swapna (International Journal of Economics and Financial Issues, 2020)
Indian economy has seen various auxiliary and key changes in financial markets. While Indian economy is on development direction, there is an extensive spread realization among all in the financial range that for such development to be practical, a corresponding deepening of financial sector must precede. And, such developing is conceivable, just when people and families are financially literate. Financial literacy is low even in advanced economies with well-developed financial markets. Financial resilience is unquestionably a significant point for analysts, investors, consultants and personal financial planners. This research investigat6es the practice of financial planning among professionals. Financial Risk tolerance is a subjective and complex phenomenon and may diverge from individual to individual. This study aims to analyze the relationship among the constructs, study the role of Financial behavior and Financial literacy as a mediator or moderator between Propensity to planning and financial well-being and finally assesses Financial Literacy score across various demographic factors. Structural equation modeling technique was used to test the variables and the hypotheses. The outcome of the study is that respondents Propensity to plan & Risk taken seems to be statistically significant. Propensity to planning male respondents are dominating. With Regard to Risk taking ability female employees are more dominating. Financial literacy, Risk taken, Financial Behavior and Financial wellbeing range all items have strong positive relationship. it shows that all are interrelated. when exogenous variables such as propensity to planning antecedents is created impact on all factors like financial behavior and Financial wellbeing. When financial behavior enacted as mediator between propensity to planning and Financial wellbeing, it shows the mediator influences on these factors. Therefore, we can infer that there is a strong role of financial behavior on all items.